2000
DOI: 10.1002/1520-6866(2000)20:4<219::aid-tcm4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparative developmental toxicity study of indium in rats and mice

Abstract: The developmental toxicity of indium was examined in both rats and mice using comparable experimental protocols. Pregnant rats received a single intravenous administration of indium trichloride (InCl(3)) at 0.4 mg In/kg, on day 9, 10, or 11 of pregnancy and their fetuses were examined on day 20. Pregnant mice were treated in the same manner at 0.8 or 1.6 mg In/kg on day 7, 8, or 9 of pregnancy and their fetuses were examined on day 18. In rats, indium caused fetal weight decrease and fetal gross malformations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…For example, the teratogenicity of cadmium in mice was decreased by bismuth-induced metallothionein (Naruse and Hayashi 1989) and caffeine (Lutz and Beck 2000). It is also a well-known fact that species differences can play a major role (Schardein 1993), as recently confirmed by studies on the developmental toxicity of indium in rats and mice (Nakajima et al 2000).…”
Section: Teratogenicitymentioning
confidence: 99%
“…For example, the teratogenicity of cadmium in mice was decreased by bismuth-induced metallothionein (Naruse and Hayashi 1989) and caffeine (Lutz and Beck 2000). It is also a well-known fact that species differences can play a major role (Schardein 1993), as recently confirmed by studies on the developmental toxicity of indium in rats and mice (Nakajima et al 2000).…”
Section: Teratogenicitymentioning
confidence: 99%
“…Silver exhibits a strong toxicity toward fish and soil microbes (Khangarot and Ray, 1988;Ratte, 1999), and Sb shows mutagenicity and induces cancerous tumors (Winship, 1987). Moreover, In is toxic to embryos in animal experiments (Nakajima et al, 2000) and Bi acts as a protoplasm poison, causing disorders of the liver, kidneys, and nervous system (Dipalma, 1988;Winship, 1983). Therefore, if this metal consumption continues to increase in the future, it may result in a new type of environmental pollution.…”
mentioning
confidence: 99%
“…Indium chloride caused developmental toxicity to the fetus when injected intravenously into pregnant rats (Nakajima et al 2000). Significant increases of fetal mortality and malformations were observed at doses of 0.4 mg In kg À1 ; however, for oral administration, there was no definitive toxicity observed up to 300 mg In kg À1 .…”
Section: Acute Effectsmentioning
confidence: 89%
“…Significant increases of fetal mortality and malformations were observed at doses of 0.4 mg In kg À1 ; however, for oral administration, there was no definitive toxicity observed up to 300 mg In kg À1 . Mice were less susceptible than rats to fetal gross malformations caused by indium, and this may depend on different toxicokinetic factors between the species (Nakajima et al 2000). Another study has shown the hemodynamic changes induced by InCl 3 in maternal rats may be detrimental to the fetus (Morvai at al.…”
Section: Acute Effectsmentioning
confidence: 99%